Human Extensive Head Skin Myiasis - M Soleimani Ahmadi; H Nasirian; AM Nazemi Gheshmi; MR Yaghoobi Ershadi (Tehran University of Medical Sciences, 2009)
"nChrysomya bezziana Villeneuve is the most important fly, which produces myiasis, exists as an obligate ectoparasite in the animals, and afflicts human. Poor hygiene and working in contaminated areas particularly during warm seasons provide a situation to infest by this parasite. Infestation in human and livestock are often observed in wounds, normal body orifices such as eyes, ears, nose, and mouth. The manifestations include pruritus, pain, inflammation, redness, eosinophilia, and secondary bacterial infections and rarely death. A 5-year-old boy with severe headache and agitation symptoms was followed up. After physical examination and endoscopy, larvae of third instar fly were obtained from his scalp. Our precise identification indicated that the flies were the C. bezziana. This is the second report of the human scalp myiasis caused by C. bezziana in Iran. This study confirmed that the old world screwworm fly was distributed in the southern of Iran and probably could be one of the most important agents of myiasis in this area.